Gamma Ray and Neutron Radiation effects on the electrical and structural properties of n-ZnO/p-CuGaO2 Schottky Diode - Gamma Ray and Neutron Radiation effects on the electrical and st; Fuei Pien Chee; Rosfayanti Rasmidi; Afishah Alias; Saafie Salleh; Khairul Anuar Mohd Salleh; Abi Muttaqin Jalal Bayar (IOP Science, 2020)
This research focuses on the radiation tolerance of ZnO and CuGaO2 based semiconductor application for space borne application. In this research, n-ZnO/p-CuGaO2 based semiconductor devices were fabricated and exposed to gamma rays with increasing total ionizing dose (TID) and neutron fluence at different flux. Based on the I-V properties, the decrease in the turn-on voltage of the diode is noticeable with increasing radiation dose for both gamma and neutron flux exposure. The maximum turn-on-voltage of the fabricated diode was shown to be 1.5 V. Exposure towards gamma, shows that the turn-on is increased to 4.7 V at 200 kGy. However, the effect of neutron flux at 6.5 × 1015 n cm−2 shows a small significant effect on the turn on voltage of 1.7 V after irradiation. Results show moderate mitigation towards irradiation, indicating that n-ZnO/p-CuGaO2 thin film is capable of withstanding harsh radiation environment while still retaining its semiconductor as the changes in band gap ranges between 3 eV to 4 eV at post-irradiation.